1992
DOI: 10.1128/jvi.66.2.956-965.1992
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies to the spike protein of feline infectious peritonitis virus mediate antibody-dependent enhancement of infection of feline macrophages

Abstract: Antibody-dependent enhancement of virus infection is a process whereby virus-antibody complexes initiate infection of cells via Fc receptor-mediated endocytosis. We sought to investigate antibody-dependent enhancement of feline infectious peritonitis virus infection of primary feline peritoneal macrophages in vitro. Enhancement of infection was assessed, after indirect immunofluorescent-antibody labelling of infected cells, by determining the ratio between the number of cells infected in the presence and absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
147
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(157 citation statements)
references
References 37 publications
9
147
1
Order By: Relevance
“…This indicates that a Th1 type immune response may not be essential for the generation of neutralizing antibodies against SARS-CoV. Although our results suggest that priming with DNA vaccines and boosting with S-peptide produced by E. coli was successful in the generation of neutralizing antibody against SARS-CoV, further experiments using infection models to evaluate its protective immunity are warranted, since anti-spike antibodies have been shown to enhance the infectivity of coronaviruses in some cell culture systems, as occurred with SARS-CoV and feline infectious peritonitis virus [33,34]. The present observation may have major practical value, such as immunization of civet cats, as production of recombinant proteins from E. coli is far less expensive than production of recombinant proteins using eukaryotic systems such as transfection of cell lines or DNA vaccines.…”
Section: Groupsmentioning
confidence: 87%
“…This indicates that a Th1 type immune response may not be essential for the generation of neutralizing antibodies against SARS-CoV. Although our results suggest that priming with DNA vaccines and boosting with S-peptide produced by E. coli was successful in the generation of neutralizing antibody against SARS-CoV, further experiments using infection models to evaluate its protective immunity are warranted, since anti-spike antibodies have been shown to enhance the infectivity of coronaviruses in some cell culture systems, as occurred with SARS-CoV and feline infectious peritonitis virus [33,34]. The present observation may have major practical value, such as immunization of civet cats, as production of recombinant proteins from E. coli is far less expensive than production of recombinant proteins using eukaryotic systems such as transfection of cell lines or DNA vaccines.…”
Section: Groupsmentioning
confidence: 87%
“…Accumulated data suggest that antibodies against the FIPV S protein fail to protect cats from FIPV challenge and enhance virus replication in the host through antibody-dependent enhancement (ADE) [69][70][71][72][73]. It has been reported that antibodies that neutralize most human SCoV isolates enhance entry of a SCoV isolate from the civet in the cell culture level [74], but it is unclear whether ADE occurs in animals that are immunized with SCoV vaccine candidates.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the precise mechanism of this liver inflammation has not been clarified. Feline infectious peritonitis virus (FIPV), another member of the coronaviruses, exhibited enhanced FIPV infection into monocytes/macrophages through viral-specific antibody binding to the Fc receptors of these cells, and caused enhanced inflammation [31]. However, there is no evidence that NT antibodies against SARS-CoV cause antibody-dependent enhancement, and correlation between inflammation and antibodydependent enhancement by MVA/S vaccination has not yet been established.…”
Section: Discussionmentioning
confidence: 99%